1997
DOI: 10.1038/nm0797-738
|View full text |Cite
|
Sign up to set email alerts
|

Fas ligand expression in islets of Langerhans does not confer immune privilege and instead targets them for rapid destruction

Abstract: Fas ligand is believed to mediate immune privilege in a variety of tissues, including the eye, testis, and a subset of tumors. We tested whether expression of Fas ligand on pancreatic islets either following adenoviral or germline gene transfer could confer immune privilege after transplantation. Islets were infected with an adenoviral vector containing the murine Fas ligand cDNA (AdFasL), and were transplanted into allogenic diabetic hosts. Paradoxically, AdFasL-infected islets underwent accelerated neutrophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
246
5
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 436 publications
(267 citation statements)
references
References 40 publications
15
246
5
1
Order By: Relevance
“…26 In contrast with these experimental findings, the presence of FasL on the surface of allogenic pancreatic islets failed to protect these islets from allogenic rejection and this reaction was found to involve the formation of a granulocytic infiltrate. 22 Introduction of human or mouse FasL cDNA into murine tumor cells did not affect tumor growth in vitro but caused rejection of the tumor by infiltrating neutrophils with subsequent induction of tumorspecific protective immunity. 21 More recent data indicate that adenovirus-mediated gene transfer of mouse FasL induced tumor regression in animal models implanted with Fas-positive and -negative tumor cells.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…26 In contrast with these experimental findings, the presence of FasL on the surface of allogenic pancreatic islets failed to protect these islets from allogenic rejection and this reaction was found to involve the formation of a granulocytic infiltrate. 22 Introduction of human or mouse FasL cDNA into murine tumor cells did not affect tumor growth in vitro but caused rejection of the tumor by infiltrating neutrophils with subsequent induction of tumorspecific protective immunity. 21 More recent data indicate that adenovirus-mediated gene transfer of mouse FasL induced tumor regression in animal models implanted with Fas-positive and -negative tumor cells.…”
Section: Discussionmentioning
confidence: 97%
“…First, Seino et al 21 showed that introduction of FasL cDNA into murine tumor cells did not affect growth in vitro but caused rejection in vivo. Further, Kang et al 22 reported that transplantation of islets of Langerhans infected with an adenoviral vector containing FasL into allogenic diabetic hosts underwent accelerated rejection. Transgenic expression of CD95 ligand on islet ␤ cells induced a granulocytic infiltration but did not confer immune privilege upon islet allografts.…”
Section: Correspondence: C Qian or J Prietomentioning
confidence: 99%
“…While allogeneic pancreatic islands transplanted together with syngeneic CD95L expressing myoblasts were tolerated, 7 allogeneic CD95L expressing pancreatic b cells were rejected due to increased neutrophil infiltration. 8 Lack of immunogenicity of tumors and resistance towards T cell attacks were also correlated with the expression of CD95L on tumor tissues. Such tumors were shown to kill CD95-positive cells in vitro.…”
mentioning
confidence: 95%
“…111 Presumably, the combination of all these mechanisms predispose the islets to environmental damage both during culture and at the transplantation site, where inflammation is likely to occur shortly after implant even before alloimmune response starts. Potential approaches to avoid this situation can include the perfusion of the organs with solutions containing chemical inhibitors of apopto- Immunoregulatory genes Indoleamine 2,3-dioxygenase 222 CTLA-4Ig 203 Fas ligand 209 (although in a number of reports Fas ligand was not protective: 248 ) Adenoviral E3 genes 210 Autoantigen transfer GAD 270 Others Adenovirus E3 proteins 271 Orally administered putative autoantigens (insulin, GAD) 272À274 CD152 275 Therapeutics for type I diabetes mellitus R Bottino et al sis (ZVAD-fmk) as well as antiapoptotic genes like bcl-2, bcl-xL, and enzymes that break down, or prevent, the formation of free-radicals such as catalase, thioredoxin, heme-oxigenase-1 and superoxide dismutase. [112][113][114][115][116][117] Some of these antiapoptotic proteins fused to protein-transduction domains can successfully prevent apoptosis and significantly improve islet yield and survival following isolation.…”
Section: Insulin Replacement Strategiesmentioning
confidence: 99%